2013
DOI: 10.1021/jp403602v
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Push–Pull States on the Ultrafast Intersystem Crossing in Nitroaromatics

Abstract: The photochemistry of nitro-substituted polyaromatic compounds is generally determined by the rapid decay of its S1 state and the rapid population of its triplet manifold. Previous studies have shown that such an efficient channel is due to a strong coupling of the fluorescent state with specific upper receiver states in the triplet manifold. Here we examine variations in this mechanism through the comparison of the photophysics of 2-nitrofluorene with that of 2-diethylamino-7-nitrofluorene. The only differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 41 publications
6
68
0
Order By: Relevance
“…We note that these values are not from a Gaussian deconvolution but merely represent the maxima values -deconvolution in a series of solvents has been published previously. 30 The spectrum of dm-ANF in methanol has not been reported previously, although a peak absorption wavelength has been reported for this compound at 420 nm 38 and 432 nm. 34 Methanol was chosen as the solvent to illustrate the similarity of the steady-state spectra because the separation of the two fluorescence bands is clearest in this solvent.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…We note that these values are not from a Gaussian deconvolution but merely represent the maxima values -deconvolution in a series of solvents has been published previously. 30 The spectrum of dm-ANF in methanol has not been reported previously, although a peak absorption wavelength has been reported for this compound at 420 nm 38 and 432 nm. 34 Methanol was chosen as the solvent to illustrate the similarity of the steady-state spectra because the separation of the two fluorescence bands is clearest in this solvent.…”
Section: Resultsmentioning
confidence: 77%
“…We employed PBE0/6-311+G(d,p) for consistency with previous studies, and because this level of theory was found to describe the excited state properties of de-ANF reasonably well. 30 Minimum energy structures (zero imaginary frequencies) were first optimized on the ground state. Excited state minima were then identified by optimization from ground state initial guesses with the planes defined by CNC and ONO being perpendicular to the aromatic skeleton and in same plane, respectively.…”
Section: Computationalmentioning
confidence: 99%
“…Examples of molecules where ISC is important range from aldehydes [37] and small aromatic compounds like benzene, [38] naphthalene, anthracene, and their carbonylic derivatives [39][40][41][42][43][44][45][46][47][48][49][50][51] to nitrocompounds. [43,[52][53][54][55][56][57][58][59][60][61] Furthermore, ISC has been reported for thio-substituted, [62][63][64][65][66][67][68] aza-substituted, [69] bromo-substituted, [70] and canonical nucleobases. [71][72][73] From a theoretical point of view, ISC can be explained by the interaction of states of different multiplicity by spin-orbit coupling (SOC), which is a relativistic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ISC was expected to be considerably slower when the SOCs are very small, as is the case in organic molecules composed solely of light atoms of the first period. For certain classes of organic molecules, such as nitro polycyclic aromatic hydrocarbons (NPAHs)3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and the closely related nitrobenzene derivatives,15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 ISC has been measured to occur in an ultrafast sub‐picosecond timescale, challenging this paradigm.…”
Section: Introductionmentioning
confidence: 99%